Current status of vitamin D2 deficiency among children in a region of China - Liu, Jia; An, Zhihua; An, Na; Zhao, Yile; Zhang, Guying; Zhao, Deyun (Frontiers in Pediatrics, 2024)
Background Exploring current status of vitamin D2 (VD2) deficiency in hospitalized children in a region of China. Methods The detections of vitamin D (VD) and VD2 in children who visited hospital from January 2022 to May 2023 were analyzed retrospectively. Additionally, the relationships between VD2 level and gender or age were further analyzed. Furthermore, for departments with high frequency of VD detection, the VD2 deficiencies in children with different diseases were further analyzed. Results Among the different age groups, children aged 11~15 years exhibited the most severe VD2 deficiency, followed by those aged 7~10 years, 0~1 year and 2~6 years. Moreover, 25(OH)D2 levels were significantly lower in children aged 7~10 years and 11~15 years compared with 2~6 years. Gender did not have an impact on the level of 25(OH)D2. When analyzing the orthopedics, dermatology, thoracic surgery, and nephroimmunology departments' data on children's levels of 25(OH)D2, it was found that the average approximately 76.56% had levels below <1.5 ng/mL compared to individuals with levels between >15 ng/mL-100 ng/mL. The average ratio between individuals with <1.5 ng/mL versus those with <15 ng/mL was found to be 91.22%. Conclusions Children who came to hospital were severely deficient in VD2. The degree of deficiency was related to age, but there was no gender difference. The phenomenon of VD2 deficiency was reflected in children with both skeletal and non-skeletal diseases.